(untitled) (Orthodontic Journal of Nepal, 2014)
Crowding being the most common chief complaint of the patients seeking orthodontic treatment has multiple treatmentoptions. Thus the orthodontist has to choose wisely amongst the options according to the individual patient need. The presentcase report is about the correction of crowding using the combination of extraction and non-extraction modality. The upperarch was treated by expansion and the lower arch was treated using extraction of a single incisor. DOI: http://dx.doi.org/10.3126/ojn.v4i1.11314 Orthodontic Journal of Nepal Vol.4(1) 2014; 57-62